2020
DOI: 10.3390/cancers12092687
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblast Mediated Inhibition of CD8+ Cytotoxic T Cell Accumulation in Tumours: Mechanisms and Therapeutic Opportunities

Abstract: The tumour microenvironment (TME) is the complex environment in which various non-cancerous stromal cell populations co-exist, co-evolve and interact with tumour cells, having a profound impact on the progression of solid tumours. The TME is comprised of various extracellular matrix (ECM) proteins in addition to a variety of immune and stromal cells. These include tumour-associated macrophages, regulatory T cells (Tregs), myeloid-derived suppressor cells, as well as endothelial cells, pericytes and cancer-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 99 publications
0
50
0
Order By: Relevance
“…CAFs, the major component of TME, have been shown to play a key-role in creating the immune-suppression milieu [5][6][7][8]. CAFs have the ability to inhibit T cell proliferation and differentiation and to upregulate expression of PD-L1 on the tumor cells, thus leading to T cell exhaustion, driving polarization of macrophages toward a pro-tumorigenic phenotype (CD163 + ), and encouraging the influx of T regulatory cells (FOXP3 + ) and other myeloid-derived suppressor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAFs, the major component of TME, have been shown to play a key-role in creating the immune-suppression milieu [5][6][7][8]. CAFs have the ability to inhibit T cell proliferation and differentiation and to upregulate expression of PD-L1 on the tumor cells, thus leading to T cell exhaustion, driving polarization of macrophages toward a pro-tumorigenic phenotype (CD163 + ), and encouraging the influx of T regulatory cells (FOXP3 + ) and other myeloid-derived suppressor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment (TME) is the complex milieu of non-malignant cells and extra-cellular matrix components that surrounds solid tumors and it is the reciprocity of TMEtumor relations that ultimately defines the malignant behavior [5]. The TME is regarded as a major mediator of immune suppression in many solid cancers [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, several studies have pointed out that CAFs can regulate T cell activity and function in the TME by the secretion of several factors, 20 including TGF-ÎČ, ARG or IDO. Thus, to validate the physiological relevance of our data pointing out improved immunosuppressive capabilities of hypoxic CAFs, we used T1 melanoma tumor cells and the autologous LT12 CTL clone in order to test the differential effect of normoxic versus hypoxic CAF CMs on T cell cytotoxic activity.…”
Section: Hypoxia Improves the Caf-dependent Alteration Of Ctl-mediated Lysismentioning
confidence: 90%
“…10,11 Importantly, CAFs have also emerged as important regulators of the anti-tumor immune response and several studies have shown that CAFs exhibit a particular immunomodulatory proteome and secretome that can potentially regulate both innate and adaptive anti-tumor immune responses. [12][13][14] For example, CAFs can increase the recruitment and differentiation of myeloid-derived suppressive cells (MDSC), 15 regulatory T cells (Tregs) 16 or type 2 tumorassociated macrophages (TAM) within the TME, 17,18 can affect dendritic cell (DC) maturation and antigen presentation functions 19 or can alter proliferation, survival and cytolytic functions of cytotoxic T cells (CTL) 20 and natural killer (NK) cells. [21][22][23] Another component of the TME is hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…ApCAFs present antigens to T cells and affect T cell immunity [ 110 ]. ApCAFs can induce CD4+ Tregs differentiation through antigen-dependent T cell antigen receptor (TCR) ligation, reduce the anti-tumor immune response by changing the ratio of CD8+ T cells to Tregs and prevent PC cells from being monitored by immune cells [ 110 , 112 , 113 ]. According to the latest research, all three of these CAFs can transform into each other, which emphasizes the dynamic process of TME [ 114 , 115 ].…”
Section: The Role Of Fibrosis In Pcmentioning
confidence: 99%